Precautious cooperative food transportation behaviour in the weaver ant Oecophylla smaragdina (Fabricius): weaver ant's secret to efficient food delivery - Naskar, Khokan; Kumar Raut, Srimanta; Maiti Dutta, Sangita (ENTOMOLOGIA HELLENICA, 2025)
The weaver ants, Oecophylla smaragdina (Fabricius), are arboreal in habit. They typically collect prey animals either from different parts of the nest tree or from the ground around it. In the present study we observed the food-transporting behaviour of these ants in Jhalda, India (Latitude-23⁰22ʹ North and Longitude 85⁰59ʹ East), specifically focusing on those foraging on the ground. We found that, depending on the size/weight of the prey, the ants have developed a process of cooperative food transportation vertically on the tree trunk. The transport of prey, especially Camponotus compressus (Fabricius) ants, is affected by the required number of transporters acting as pullers and pushers, depending on the prey's size/weight. Simultaneously, a corresponding number of workers can be seen following the food-carrying group all along until the food is lodged into the nest. The differences in the number of workers involved in vertical food transportation are statistically significant, as are revealed by the results of a one-way ANOVA test and Tukey’s HSD test (P < 0.05).